Mass spectrometry‐based abundance atlas of ABC transporters in human liver, gut, kidney, brain and skin. Issue 23 (3rd December 2020) - Al‐Majdoub, Zubida M.; Achour, Brahim; Couto, Narciso; Howard, Martyn; Elmorsi, Yasmine; Scotcher, Daniel; Alrubia, Sarah; El‐Khateeb, Eman; Vasilogianni, Areti‐Maria; Alohali, Noura; Neuhoff, Sibylle; Schmitt, Lutz; et al.
Abstract : ABC transporters (ATP‐binding cassette transporter) traffic drugs and their metabolites across membranes, making ABC transporter expression levels a key factor regulating local drug concentrations in different tissues and individuals. Yet, quantification of ABC transporters remains challenging because they are large and low‐abundance transmembrane proteins. Here, we analysed 200 samples of crude and membrane‐enriched fractions from human liver, kidney, intestine, brain microvessels and skin, by label‐free quantitative mass spectrometry. We identified 32 (out of 48) ABC transporters: ABCD3 was the most abundant in liver, whereas ABCA8, ABCB2/TAP1 and ABCE1 were detected in all tissues. Interestingly, this atlas unveiled that ABCB2/TAP1 may have TAP2‐independent functions in the brain and that biliary atresia (BA) and control livers have quite different ABC transporter profiles. We propose that meaningful biological information can be derived from a direct comparison of these data sets.